1995
DOI: 10.1007/bf00931614
|View full text |Cite
|
Sign up to set email alerts
|

Uterine atrophy in chronic murine toxoplasmosis due to ovarian dysfunction

Abstract: Uterine atrophy is a conspicuous finding in Nya:NYLAR female mice chronically infected with Toxoplasma gondii. Administration of 17B-estradiol to infected mice induced a vigorous uterotropic response, i.e., an increase in uterine weight, in endometrial hypertrophy and proliferation, and in the activity of three estrogen-regulated uterine enzymes. These findings rule out a parasite-induced refractoriness of the uterus to estrogen and point to ovarian dysfunction (hypogonadism) as the immediate cause of the uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…10,11 At some papers on workroom animals had been exposed that infection with T. gondii due to sterility during chronictoxoplasmosis, the laboratory -animals in (rat's female) maybe foundation Endometriosis, weak-follicles, debility ovaries, leanness in the ovaries and uterus, depression in adrenal glands inflation, genital action , cessation of reproduce to failure, vascular inflammation in experimental menstrual dysplasia and mice. [12][13][14]…”
Section: Research Articlementioning
confidence: 99%
“…10,11 At some papers on workroom animals had been exposed that infection with T. gondii due to sterility during chronictoxoplasmosis, the laboratory -animals in (rat's female) maybe foundation Endometriosis, weak-follicles, debility ovaries, leanness in the ovaries and uterus, depression in adrenal glands inflation, genital action , cessation of reproduce to failure, vascular inflammation in experimental menstrual dysplasia and mice. [12][13][14]…”
Section: Research Articlementioning
confidence: 99%
“…Infectious diseases are amongst the most frequent causes for male and female reproductive pathology and infertility, in humans and animals (Bennett, Dolin, & Blaser, ; Maxie, ). Reproductive tissue tropism has been studied in the context of Trichomonas (Parsonson, Clark, & Dufty, ) , T. gondii (Lopes et al, ; Stahl, Kaneda, Tanabe, & Kumar, ), T. cruzi (Id Boufker, Alexandre, Carlier, & Truyens, ), T. brucei (Carvalho et al, ), Plasmodium (Muehlenbein, Alger, Cogswell, James, & Krogstad, ; Raji, Akinsomisoye, & Azeez, ) , Entamoeba (reviewed in [Antony and Lopez‐Po ]) and to a large extend in Leishmania (Assis, Ribeiro, Rachid, Castro, & Valle, ; Blickstein, Dgani, & Lifschitz‐Mercer, ; Cabello, Caraballo, & Millan, ; Diniz et al, ; Gonzalez, Gallego, Castaño, & Rueda, ; Mir, Fontaine, Reyes‐Gomez, Carlus, & Fontbonne, ; Schubach, Cuzzi‐Maya, Gonçalves‐Costa, Pirmez, & Oliveira‐Neto, ). Infertility can be directly associated with presence of parasites in the tissue, through triggering inflammation and tissue damage or indirectly due to systemic effects that result in impaired reproductive function.…”
Section: Organs In the Abdominopelvic Cavitiesmentioning
confidence: 99%
“…In rodents, many other parasitic infections involving protozoa, such as trypanosomiasis and toxoplasmosis (Hublart et al 1990;Tavares et al 1994;Stahl et al 1995), or involving larval tapeworms (Lin et al 1990; Morales-Montor et al 1999), have been associated with hormonal perturbations which greatly impair the sexual functions of the host. Curiously, although Akingbade et al (1990) demonstrated that the acute phase of a Plasmodium berghei infection induces a hormonal imbalance in female Wistar mice, no dysfunctions in the sexual physiology and no modifications of the genital tract were reported in infected females.…”
Section: Introductionmentioning
confidence: 98%